Pawning Online Game Accounts From a Civil Law Perspective: A Case Study - Kamila, Najma; Noor, Afif; Asari, Aang (Journal La Sociale, 2025)
The use of games today is no longer limited to mere entertainment; the function of games has expanded into sports and business. One unique aspect of games in the business world is the existence of game accounts with significant economic value. Several factors, including quality, demand, and the rarity of items within the account, influence the economic value of a game account. In its development, game accounts are no longer limited to buying and selling; recently, a business entity has utilized game accounts as collateral. This requires further examination from the property law perspective and relevant security law regarding online game accounts. This study employs a normative legal research method with a statutory approach, utilizing legal regulations and academic articles as sources of law. The research findings indicate that the owner of an online game account is merely a possessor and does not possess property rights over the account itself, as property rights are inherently tied to ownership. Ownership remains solely with the game developer/publisher, while the player only obtains a license. It is crucial to be aware of the legal limitations, as the nature of the account transfer agreement is invalid because it does not comply with the fourth element of Article 1320 of the Indonesian Civil Code, so any agreement intended to transfer an account is deemed null and void. The pawn scheme from @sytnaxgadaigame is invalid because it does not meet the principles of Security Law.